A case-control study on the temperament and Psychological mood of patients with chronic Hepatitis B. Issue 3 (July 2017) - Fındıklı, Ebru; Ateş, Selma; Kandemir, Bahar; Karaaslan, Mehmet Fatih; Camkurt, Mehmet Akif; İzci, Filiz; Durduran, Yasemin; Kardaş, Selçuk; Bitirgen, Mehmet
No abstract available